Strategi Pemasaran Buah Jeruk Siam (Citrus nobilis) (Studi Kasus di Desa Melati II Kecamatan Perbaungan Kabupaten Serdang Bedagai) - Safitri, Bella; Nurcahyani, Marizha; Rahman, Abdul (Jurnal Agrisep, 2025)
This study aims to find out EFAS and IFAS as well as the marketing strategy of siamese oranges in Melati II Village, Perbaungan District. The data analysis in this study is a descriptive analysis and a SWOT analysis. The location of this research was chosen deliberately (purposive), this research was carried out in Melati II Village, Perbaungan District.Using the Snowball Sampling method for farmers and marketing institutions, the simple random sampling method for consumer samples. Based on the results of the study, it can be concluded that the marketing strategy of chayote is an aggressive development strategy by utilizing the existing strategies of strength and opportunity. Business owners can take advantage of the combination of these two strategies, namely maintaining the quality of Siamese oranges during religious holidays (S1,O1), selling fruits directly to consumers during religious holidays (S3,O1), and retaining customers by providing discounts and good relations with stakeholders (S4,O3,S5) and being able to overcome existing weaknesses and threats, namely increasing promotions so that they can compete with other Siamese orange businesses (W1, T1). Keywords: Marketing Channels, Internal Factors, External Factors, SWOT AnalysisKeywords: Marketing Channels, Internal Factors, External Factors, SWOT Analysis